Limbic‐predominant age‐related TDP‐43 encephalopathy neuropathologic change and microvascular pathologies in community‐dwelling older persons. (23rd February 2021) - Agrawal, Sonal; Yu, Lei; Kapasi, Alifiya; James, Bryan D.; Arfanakis, Konstantinos; Barnes, Lisa L.; Bennett, David A.; Nag, Sukriti; Schneider, Julie A.
Abstract: Limbic‐predominant age‐related transactive response DNA‐binding protein 43 (TDP‐43) encephalopathy neuropathologic change (LATE‐NC) and microvascular pathologies, including microinfarcts, cerebral amyloid angiopathy (CAA), and arteriolosclerosis are common in old age. A relationship between LATE‐NC and arteriolosclerosis has been reported in some but not all studies. The objectives of this study were to investigate the frequency of co‐occurring LATE‐NC and microvascular pathologies and test the hypothesis that arteriolosclerosis, specifically, is related to LATE‐NC in brains from community‐dwelling older persons. Analyses included 749 deceased participants with completed data on LATE‐NC and microvascular pathology from 3 longitudinal clinical pathologic studies of aging. Given the specific interest in arteriolosclerosis, we expanded the examination of arteriolosclerosis to include not only the basal ganglia but also two additional white matter regions from anterior and posterior watershed territories. Ordinal logistic regression models examined the association of microvascular pathology with LATE‐NC. LATE‐NC was present in 409 (54.6%) decedents, of which 354 (86.5%) had one or multiple microvascular pathologies including 132 (32.3%) with moderate‐severe arteriolosclerosis in basal ganglia, 195 (47.6%) in anterior watershed, and 144 (35.2%) in posterior watershed; 170 (41.5%) with moderate‐severe CAA, and 150 (36.6%) with microinfarcts. In logistic regression models, only posterior watershed arteriolosclerosis, but not other regions of arteriolosclerosis was associated with a higher odds of more advanced LATE‐NC stages (Odds Ratio = 1.12; 95% Confidence Interval = 1.01–1.25) after controlling for demographics, AD, and other age‐related pathologies. Capillary CAA, but not the severity of CAA was associated with an increased odds of LATE‐NC burden (Odds Ratio = 1.71; 95% Confidence Interval = 1.13–2.58). Findings were unchanged in analyses controlling for APOE ε4, vascular risk factors, or vascular diseases. These findings suggest that LATE‐NC with microvascular pathology is a very common mixed pathology and small vessel disease pathology may contribute to LATE‐NC in the aging brain. Abstract : LATE‐NC with microvascular pathology is a very common mixed pathology and small vessel disease pathology may contribute to LATE‐NC in the aging brain.